522 A meta-ethnography of how children and young people with chronic pain and their families experience and perceive pain services and treatments and living with pain. (17th August 2022) - France, Emma; Turley, Ruth; Uny, Isabelle; Forbat, Liz; Caes, Line; Jordan, Abbie; Noyes, Jane; Bianchim, Mayara Silveira
Abstract : Aims: To investigate how children and young people (CYP) with chronic pain and their families perceive and experience pain-related treatments and services and living with pain. Methods: A meta-ethnography was conducted with involvement of CYP with chronic pain and their parents (n = 22). Systematic review methods included comprehensive searches of 12 bibliographic databases to identify qualitative and mixed-methods studies with CYP aged 3 months to 18 years with chronic pain and their families. We included the most relevant, conceptually-rich publications and developed new interpretations and theoretical findings. Results: Forty-two publications representing the views of 561 CYP with chronic pain and their family members were included in the synthesis. Chronic pain and its management have wide-ranging deleterious impacts on the lives of CYP and family members, often dominating family life and altering family dynamics. Parents express a sense of responsibility for managing their child's chronic pain. Particularly for children who cannot communicate their pain, parents become experts in assessing their child's pain. Children and young people with more recent onset of chronic pain and their parents express the desire for objective, credible diagnoses and curative treatment for their pain, reflecting a medical model of pain which assumes a physical cause. Without a meaningful, credible diagnosis, parents can feel blamed for causing their child's pain and may feel labelled as a 'dysfunctional' family. A diagnosis can legitimise children's chronic pain and facilitate access to treatment. Over time, without a diagnosis indicating pathology, families begin to move towards improving child and family quality of life and managing pain, despite continuing anxiety regarding the unknown cause of pain. Even when a clear explanation for the pain is provided, there are numerous barriers to effective pain management. These include families losing trust and faith in health services in relation to their perceptions that healthcare professionals' knowledge of, and ability to accurately assess, chronic pain is poor; perceived prejudice/racism in relation to CYP who are denied opioids for pain relief; and when CYPs perceive that healthcare professionals do not believe their pain is real. Consequently, children avoid attending services when they need them and may resort to self-management of pain due to a perceived lack of other credible treatment options. Other barriers to effective pain management concern difficulties for families accessing and navigating services, e.g., due to the lack of specialist pain services or when CYP with concurrent complex conditions, like cerebral palsy and co-occurring chronic pain, are unable to meet the referral criteria for a specific pain service and/or fall between gaps in services. Conclusion: Findings highlight the importance of healthcare professionals acknowledging: (1) the expertise of CYP and parents who live with pain, and (2) the credibility of the child's pain and adopting a systemic family approach to pain management. A trusting relationship between families and professionals is important for engagement with effective pain management. Future high-quality research is urgently needed to investigate safe, effective treatments in order to advance children's chronic pain management and to explore how to better support families' psychosocial needs.